Comprehensive Physiology 2015
DOI: 10.1002/cphy.c150022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics and Heart Failure

Abstract: Mitochondrial dynamics, fission and fusion, were first identified in yeast with investigation in heart cells beginning only in the last 5–7 years. In the ensuing time it has become evident that these processes are not only required for healthy mitochondria, but also, that derangement of these processes contributes to disease. The fission and fusion proteins have a number of functions beyond the mitochondrial dynamics. Many of these functions are related to their membrane activities, such as apoptosis. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 203 publications
(273 reference statements)
0
20
1
Order By: Relevance
“…The balance between fission and fusion regulate the morphology of mitochondria. Defective mitochondrial dynamics has also been identified as a feature of heart failure (Knowlton and Liu, ) and diabetic cardiomyopathy (Galloway and Yoon, ). Hausenloy and colleagues have further reported that the promotion of fusion (and inhibition of fission) is cardioprotetive against ischaemia reperfusion injury (Ong et al, ).…”
Section: Cryo‐em and Spa Techniques Enter A New Era For Protein Strucmentioning
confidence: 99%
“…The balance between fission and fusion regulate the morphology of mitochondria. Defective mitochondrial dynamics has also been identified as a feature of heart failure (Knowlton and Liu, ) and diabetic cardiomyopathy (Galloway and Yoon, ). Hausenloy and colleagues have further reported that the promotion of fusion (and inhibition of fission) is cardioprotetive against ischaemia reperfusion injury (Ong et al, ).…”
Section: Cryo‐em and Spa Techniques Enter A New Era For Protein Strucmentioning
confidence: 99%
“…14 The mitochondrial dysfunction that has been correlated to the bioenergetic collapse seen in heart failure derives largely from studies in LV disease, 15 and is characterized by depressed oxidative phosphorylation, 16,17 a metabolic switch from fatty acid oxidation (FAO) to glycolysis, 18 lipid accumulation and lipotoxicity, 19 and changes in mitochondrial morphology and dynamics. [20][21][22] Some of these changes have been recapitulated in models of RV failure, particularly the switch from FAO to glycolysis. [23][24][25] Beyond this, few studies directly compare the metabolic differences between the LV and RV in health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance leads to cellular dysfunction ( van der Bliek et al ., 2013 ). In recent studies, the association between mitochondrial dynamics and cardiovascular disease has been explored ( Knowlton and Liu, 2015 ), and mitochondrial dysfunction as a major cause of various diseases has been postulated ( Archer, 2013 ).…”
Section: Introductionmentioning
confidence: 99%